Perancangan & Implementasi Sistem Pengarsipan Surat Masuk & Surat Keluar pada Kelurahan Danga Menggunakan Metode Alphabetical Filing, Chronology System dan Numerical Filing - Dae, Sinklaus Patrezki; Nurdewanto, Bambang (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study delves into the implementation of a computer-based archiving system for incoming and outgoing letters in Kelurahan Danga, Kota Mbay. Alphabetical filing, chronological system, and numerical filing methods are employed to enhance the efficiency and effectiveness of letter management. Evaluation using the System Usability Scale (SUS) indicates that the system meets standards with a score of 78.9, falling into the "Acceptable" category, with a grade of "A-" and an "Excellent" rating. The system significantly contributes to expediting data retrieval, avoiding delays, and improving productivity in Kelurahan Danga.